Analysis of Shiite Political Thought in Iran and Its Influence in Indonesia - Maulana Hayatullah; Supra; Syafiuddin; Moh Arrofior Rohman; Novan Gonzales (Jurnal Lentera Insani, 2025)
This study aims to investigate the process of ideological transfer, the instruments of soft power employed by Iran, and the responses of Indonesian society and the state to the presence of Shi'ite political narratives within a context of religious plurality. This study uses library research as its primary approach to deeply and critically analyse the dialectic of Shiite political thought in Iran and its transnational influence in Indonesia. The conclusions affirm that the contestation of ideology, identity, and civil rights within Muslim societies is not merely a matter of theology or political export, but rather a reflection of deeper struggles over how the state, religion, and citizens manage diversity and power in the global era. The Iranian model of al-Faqih al-Qadha'i (the rule of the jurist) has indeed shaken the old boundaries of Islamic authority and offered inspiration for resistance against injustice. Indonesia has instead triggered polarisation, stigmatisation, and even discrimination, reopening old wounds of fragile diversity. However, the experience of the Shia both as a marginalised minority and as part of a global narrative of resistance serves as a provocative reminder that Indonesia's strength as a nation does not lie in the stability of a single identity, but in its collective ability to transform differences into energy for dialogue, innovation, and reconciliation for a more just and civilised national future.